METAPHORS AND PRAGMATIC IN MINANGKABAU LANGUAGE - Yanti Riswara (Balai Bahasa Provinsi Riau, 2012)
This article aims at describing the using of metaphors and pragmatics patterns in Minangkabau language. The usage of such words with metaphors and pragmatics might be found in many every day living contexts. This research is a qualitatif research. The data collected during an intensive survey by using the listening method (metode simak) followed by tapping technique. Based on the data analysis, it can be concluded that a culture could influence the using of metaphors in line with the using of pragmatics. The native speakers of Minangkabau language have the ability to understand what they are spoken about even by using the metaphors. Exactly, there is no much doubts of when and where they turn to change the use of literal meanings to the metaphorical ones and vise versa in their every day language, as well as they understand the tw o kinds of meaning perfectly according to context in which the speech act taken place